2022
DOI: 10.3758/s13415-022-01014-y
|View full text |Cite
|
Sign up to set email alerts
|

From skinner box to daily life: Sign-tracker phenotype co-segregates with impulsivity, compulsivity, and addiction tendencies in humans

Abstract: Pavlovian conditioning holds the potential to incentivize environmental cues, leading to approach behavior toward them, even outside our awareness. Animal models suggest that this is particularly true for the so-called sign-tracker (ST) phenotype, which is considered to reflect a predisposition toward developing addiction-related behaviours. Despite its potential clinical relevance, few studies have demonstrated the translational validity of this model, likely due to difficulties in studying Pavlovian processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…Crucially, whereas goal-trackers and intermediate animals performed fewer dysfunctional eOLPs once the shock contingency was removed, sign-trackers did not decrease their dysfunctional checking behaviour after the contingency between maladaptive checking and shock delivery had been decoupled. This aligns with the notion of persistent, dysfunctional behavioural aberrations analogous to compulsive checking in humans, as well as pointing to the phenotypic susceptibility of sign-tracking subjects to engage in compulsive behaviour, as described in the addiction literature (Flagel et al, 2009 ; Tomie et al, 2008 ; Robinson et al, 2018 ; Schettino et al, 2022 ). This emerging research hence supports the utility of the ORT as an objective translational tool for illuminating underlying processes akin to the maladaptive checking observed in OCD patients, allowing complementary studies to be conducted in rodents (which would allow for causal manipulations of checking through pharmacological and neural manipulations) and humans (both healthy participants and patients, where there is potential for functional imaging and subjective, in addition to objective, measures).…”
Section: Pharmacological Models Of Ocdsupporting
confidence: 83%
“…Crucially, whereas goal-trackers and intermediate animals performed fewer dysfunctional eOLPs once the shock contingency was removed, sign-trackers did not decrease their dysfunctional checking behaviour after the contingency between maladaptive checking and shock delivery had been decoupled. This aligns with the notion of persistent, dysfunctional behavioural aberrations analogous to compulsive checking in humans, as well as pointing to the phenotypic susceptibility of sign-tracking subjects to engage in compulsive behaviour, as described in the addiction literature (Flagel et al, 2009 ; Tomie et al, 2008 ; Robinson et al, 2018 ; Schettino et al, 2022 ). This emerging research hence supports the utility of the ORT as an objective translational tool for illuminating underlying processes akin to the maladaptive checking observed in OCD patients, allowing complementary studies to be conducted in rodents (which would allow for causal manipulations of checking through pharmacological and neural manipulations) and humans (both healthy participants and patients, where there is potential for functional imaging and subjective, in addition to objective, measures).…”
Section: Pharmacological Models Of Ocdsupporting
confidence: 83%
“…Cope et al [7] measured behavioural impulsivity using the Barratt Impulsivity Scale and found that higher scores were associated with sign-tracking behaviour in young adults, in accordance with Garofalo & di Pellegrino [16]. Using an experience sampling design to investigate real-life attribution of high incentive salience to reward-related cues, Schettino et al [35] found that high levels of impulsivity, obsessive-compulsive tendencies and addiction-prone tendencies predicted higher attractiveness of the sign, compared with the goal. Colaizzi et al [6] measured externalising tendencies using parent-report questionnaires (Child Behaviour Checklist and Early Adolescent Temperament Questionnaire), and reported increased ADHD-like symptoms, increased fear, and lower inhibitory control in ST, though they found no group differences in self-reported or behavioural measures of inhibition and impulsivity.…”
Section: Discussionmentioning
confidence: 88%
“…After reading and signing the informed consent, participants were asked to complete a series of online questionnaires (via Qualtrics) assessing socio-demographic and medical information (e.g., sex, age, education level, medical or psychiatric diagnosis, substance use). If inclusion criteria were met, participants were subsequently evaluated for dispositional psychological characteristics that have been shown to co-segregate with ST/GTs (e.g., impulsiveness, obsessive-compulsive tendencies, [32]) (see S1 for details on the administered questionnaires). Our research protocol consisted of two separate sessions: during the rst, behavioral data were acquired, while the second was entirely dedicated to the RSFC data acquisition.…”
Section: Methodsmentioning
confidence: 99%